Clinical Atlas of Ocular Oncology - Damato, Bertil E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Many ocular tumours are life-threatening or associated with lethal syndromes but can be difficult to diagnose because of their rarity and diversity. Unlike conventional atlases, this book contains a format that orders lesions according to their colour and ocular location to help readers quickly find the information they need even when they do not already know the diagnosis. Multimodal imaging results are presented to help provide a definitive diagnosis when slit-lamp and ophthalmoscopic findings are inconclusive. The seemingly random organisation of cases enables self-assessment by trainees. Written for optometrists and ophthalmologists, Clinical Atlas of Ocular Oncology is an essential resource for practitioners at any stage in their career.
Chapter 1. Extraocular Lesions -- Chapter 2. Anterior Intraocular Lesions -- Chapter 3. Vitreous,- Chapter 4. Optic Disc Lesions -- Chapter 5. Neurosensory Retinal Lesions -- Chapter 6. Retinal Pigment Epithelial Lesions -- Chapter 7. Choroidal Lesions -- Chapter 8. Suprachoroidal Lesions -- Chapter 9. Scleral Lesions. .
Keywords: Ophthalmology; Oncology; Ophthalmology; Oncology; Eye Neoplasms; Atlases